Monitoring Land Subsidence Using Remote Sensing - Fabris, Massimo; Cenni, Nicola; Fiaschi, Simone (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In this book are reported nine works related to land subsidence monitoring using remote sensing techniques. Land subsidence is a common phenomenon in many regions of the world, where it causes degradation of local ecosystems and disruption of economic activities. Its effects are more evident in densely populated areas in particular in low-lying territories such as river deltas and coastal areas where the combination of land subsidence and sea level rise increases the flooding risk. For this reason, the monitoring of ground deformations is a crucial step to obtain important information for the development of risk mitigation strategies. In the presented papers, the characteristics of land subsidence occurring in different study areas are described, and recent developments in the used methodologies for the monitoring of the ground displacements are discussed and validated also by means of ground-based data. Moreover, advantages and disadvantages of the adopted techniques are highlighted. The outcomes of these research works can provide national and local authorities with useful information for the implementation of integrated monitoring systems in the areas most affected by land subsidence.